Exploring Religious Practices and Religious Identity Among Yemeni Postgraduate Students in Malaysia - Najib Saif Mubarak Al Aghbas; Mohd Faizal Kasmani (Universiti Sains Islam Malaysia, 2024)
Ulum Islamiyyah:Malaysian Journal of Islamic Sciences Volume 36 No 1 Page (61-72)